Report on proposed new interior design of Stadium Negara historical and sports gallery for Permodalan Nasional Berhad (PNB) at Jalan Stadium, 50150 Kuala Lumpur / Nurul Izzati Aina Solahuddin - Solahuddin, Nurul Izzati Aina (Faculty of Architecture, Planning and Surveying, 2011)
The final project of interior design for diploma exhibits a student’s understanding of the processes of interior design from the basic to the presentation of design proposal. The final project for my final semester is to proposed new interior design of Stadium Negara historical and sports gallery for Permodalan Nasional Berhad (PNB) at Jalan Stadium, 50150 Kuala Lumpur. The concept and image play a role for both interior and exterior to look good and will be able to attract more tourists and visitors who were always keen in our aesthetic values in architecture. There were several researches done to get information for this final project such as site analysis, building analysis, interview, observation and case studies. All these studies have a purpose of identifying the existing weaknesses and also attempt to solve some of the problems that appear. These investigations will be implemented in the design process with the intention to gain an attractive design that suit for the gallery and client’s demand in terms of function and aesthetic value.